2019
DOI: 10.1186/s12884-019-2239-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors’ importance on adverse pregnancy and neonatal outcomes in women aged 40 years or older

Abstract: BackgroundWomen of advanced age (40 years or older) are generally, at risk for pregnancy and delivery related problems. In addition, there is limited knowledge on being of advanced age and having been given Assisted Reproductive Treatment (ART) and its association with negative obstetric outcomes. Therefore, data from the Swedish Medical Birth Register was used to investigate pregnancy and neonatal outcomes for women aged 40 or more who had given birth. The secondary aim was to compare the obstetric outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
48
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 23 publications
6
48
1
1
Order By: Relevance
“…The location of the study may represent the inconsistency of scientific conditions and levels as well as various races of participants, resulting in heterogeneity among studies. Furthermore, the average age of pregnant women and the proportion of primipara can represent the physical and mental condition of pregnant women to some extent [55]. In addition, we found that WeChat interventions were more effective than other types of TM tools on more outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…The location of the study may represent the inconsistency of scientific conditions and levels as well as various races of participants, resulting in heterogeneity among studies. Furthermore, the average age of pregnant women and the proportion of primipara can represent the physical and mental condition of pregnant women to some extent [55]. In addition, we found that WeChat interventions were more effective than other types of TM tools on more outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…For instance, Jolly et al [ 43 ] identified gestational diabetes mellitus as significantly common in the older age groups. Other studies have also found the risk of negative pregnancy outcomes among older women [ 44 47 ]. Ageing reproductive system and an ageing body have been identified as some of the factors that increase pregnancy-related risks in older women [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…If this leads to a growth in the size of the single-parent-by choice group, further research on this group is needed. However, the results of our study indicate that health care needs to give more attention to the ever-growing population of single mothers, not just to any special subgroup (21,39,41).…”
Section: Discussionmentioning
confidence: 70%
“…The underestimation of the impact of age-related factors on female fertility and the overestimation of the use of ART in overcoming age-related infertility [48][49][50][51][52][53] probably contribute to the postponement of childbearing. The substantial risks for both the woman and the child associated with giving birth at advanced maternal age 21,39,54 call for appropriate physician counseling of older women who are considering ART 55 . It appears that education about fertility and infertility should be given a more prominent place in health programs focused on how to prevent sexually transmitted diseases and unwanted pregnancies in schools and health settings.…”
Section: Discussionmentioning
confidence: 99%